-4x+1=3(5x-4)-6

Simple and best practice solution for -4x+1=3(5x-4)-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x+1=3(5x-4)-6 equation:



-4x+1=3(5x-4)-6
We move all terms to the left:
-4x+1-(3(5x-4)-6)=0
We calculate terms in parentheses: -(3(5x-4)-6), so:
3(5x-4)-6
We multiply parentheses
15x-12-6
We add all the numbers together, and all the variables
15x-18
Back to the equation:
-(15x-18)
We get rid of parentheses
-4x-15x+18+1=0
We add all the numbers together, and all the variables
-19x+19=0
We move all terms containing x to the left, all other terms to the right
-19x=-19
x=-19/-19
x=1

See similar equations:

| 2(2x-3)-7=-9 | | -44=5(x-2)+1 | | 4x-15=-4x+57 | | 2(3x+4)-8=36 | | 3x+2=9-5x | | √y+10=y+10 | | 2x+4=44−2x | | 12k=97 | | 1/2x+2/3=8 | | 5z+0=25 | | 3y+21=33 | | 0.4(3x-1)=0.5(x+1) | | a^2=3a+8 | | 60+2x=120–x | | 60+2x=120–x, | | 3x–57=88 | | 15p^2+5p=20 | | 15^2p+5p=20 | | 2/3x-5=4+x | | (x+9)/5=-9 | | 18-4y=10 | | (7)(17.5)=3x | | -3(3p+6)-2(2-14p)=3(4+6p) | | -5(-2x+8)-8(-5-5x)=48+51x | | 8x+5x+3+7=10x+4+2x | | 6x+5+5x-2=5x+6x-11 | | 5b²+4=-12b | | 4/6w=-4 | | 10x10^2x=6 | | 5(4r)=-80 | | 5a²+15a=0 | | -3x+11-5=11 |

Equations solver categories